2014
DOI: 10.1158/0008-5472.can-13-2053
|View full text |Cite
|
Sign up to set email alerts
|

Neuromedin U: A Candidate Biomarker and Therapeutic Target to Predict and Overcome Resistance to HER-Tyrosine Kinase Inhibitors

Abstract: Intrinsic and acquired resistance to HER-targeting drugs occurs in a significant proportion of HER2-overexpressing breast cancers. Thus, there remains a need to identify predictive biomarkers that could improve patient selection and circumvent these types of drug resistance. Here, we report the identification of neuromedin U (NmU) as an extracellular biomarker in cells resistant to HER-targeted drugs. NmU overexpression occurred in cells with acquired or innate resistance to lapatinib, trastuzumab, neratinib, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…Recently, expression of the neuropeptide neuromedin U was associated with a poor prognosis in HER2-overexpressing breast cancer and has been shown to correspond with resistance to HER-targeting agents, including neratinib in vitro. It was suggested that neuromedin U acts through the chaperone heat shock protein 27 to aid HER2 stability 77. As with lapatinib,46 we observed a reactivation of HER3 and AKT phosphorylation after 24 hours of neratinib treatment in HER2-positive breast cancer cells, although we did not assess whether this was NRG1-dependent 26.…”
Section: Introductionmentioning
confidence: 63%
“…Recently, expression of the neuropeptide neuromedin U was associated with a poor prognosis in HER2-overexpressing breast cancer and has been shown to correspond with resistance to HER-targeting agents, including neratinib in vitro. It was suggested that neuromedin U acts through the chaperone heat shock protein 27 to aid HER2 stability 77. As with lapatinib,46 we observed a reactivation of HER3 and AKT phosphorylation after 24 hours of neratinib treatment in HER2-positive breast cancer cells, although we did not assess whether this was NRG1-dependent 26.…”
Section: Introductionmentioning
confidence: 63%
“…Several functional assays have revealed that overexpression or treatment of cancer cells with exogenous NmU increases cell proliferation, migration, invasion, and resistance to loss of anchorage-induced apoptosis, while knockdown of NmU expression has the opposite effects (128,(131)(132)(133). These results were confirmed in in vivo assays, where NmU overexpression was shown to enhance tumor formation and metastasis, as well as possibly inducing cachexia (130 ).…”
Section: Cancermentioning
confidence: 86%
“…Moreover, overexpression of NmU was associated with worse prognosis (45,133 ). NMUR2 has been detected in human pancreatic cancer samples and canine peripheral nerve sheath tumors, suggesting that the autocrine/paracrine NmU-NMUR2 axis might be important for the development and/or progression of these tumors (131,134 ).…”
Section: Cancermentioning
confidence: 99%
“…Since NmU has cardiovascular effects [70,71] as well as being indicated in cancer [7274], it is of great interest whether prolonged exposure to our analogs may have related side effects. To assess such possible effects we measured levels of lysophosphatidic acid (LPA, (20:4)-1-arachidonoyl-2-hydroxy-sn-glycero-3-phosphatidic acid; (18:2)-1-linoleoyl-2-hydroxy-sn-glycero-3-phosphatidic acid; and (18:1)-1-oleoyl-2-hydroxy-sn-glycero-3-phosphatidic acid) in the plasma of animals treated frequently (1603 nmoles/kg; every 2 or 4 or 7 days for 21 days) with NM4A or NM4-C 16 using a previously described LC-ESI-MS/MS-based method [7578].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 6C, prolonged treatment of DIO mice with NM4A does not increase plasma levels of LPA suggesting that therapy should have no negative effects on obese patients that are prone to atherosclerosis and diabetes development. Since LPA is also indicated in cancer, these results also suggest that use in obese cancer patients or people who are not aware they have cancer, should be relatively safe, which may be of concern due to the connection of NmU with breast and pancreatic cancers [7274]. In the case of NM4-C 16 slightly elevated levels of (20:4) were observed which may be of concern since this particular lipid was shown to enhance progression of atherosclerosis in animal model [82].…”
Section: Resultsmentioning
confidence: 99%